2022
DOI: 10.1002/ccr3.5524
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent severe neutropenia following doxycycline use in a young healthy woman

Abstract: A 29‐year‐old woman was hospitalized for fever, pharyngitis, and severe neutropenia after recent use of doxycycline and other antimicrobials. Three years later, she again presented with severe neutropenia after recent doxycycline use. Diagnostic workups were unyielding. This is only the second published case of severe neutropenia associated with doxycycline use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…DOI: https://doi.org/10.22225/wmj.7.2.4753.60-69 had no discernible influence on the improvement of blood oxygen saturation of patients with severe influenza (11) .…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…DOI: https://doi.org/10.22225/wmj.7.2.4753.60-69 had no discernible influence on the improvement of blood oxygen saturation of patients with severe influenza (11) .…”
Section: Discussionmentioning
confidence: 90%
“…In particular, I think it is important to properly define the terms 'inflammation' and 'infection'. Just by reading the definition of inflammation on Wikipedia, we learn that 'inflammation is part of the complex biological response of vascular tissue to noxious stimuli, such as pathogens, damaged cells, or irritants (11) . This Result of two randomized control trials has shown that corticosteroid use can reduce the incidence of treatment failure and shorten the time to clinical stability in patients with community-acquired pneumonia.…”
Section: D)mentioning
confidence: 99%